Analysis of Halal Certification Implementation Strategy for MSMEs in Banyuwangi Regency (Study on Food and Beverage MSMEs in Banyuwangi Regency) - Bibit Wahyudi (IJIEF: Indonesian Journal of Islamic Economics and Finance, 2024)
Nowadays, the strengthening of halal chain development is also associated with various industrial production activities. In Banyuwangi Regency, related to the institution that coordinates the running of halal economic programs for food and beverage MSMEs, it is under the auspices of the Micro Business and Trade Cooperative Office, the Banyuwangi Regency Industry and Trade Office. In addition to the MSME and IKM offices, it was also assisted by the Banyuwangi Ministry of Religion and also MSME associations in Banyuwangi Regency. This study aims to find out the strategy for the implementation of halal certification, socialization of halal certification in MSMEs and find out the inhibiting and supporting factors in the implementation of halal certification in MSMEs in Banyuwangi Regency. This study uses a qualitative descriptive method with a case study and SWOT approach. The results of this study show that the strategy used: first, by providing official offices. Second, take steps to develop human resources. Third, building relationships. Fourth, socializing halal certification. The socialization used: carried out by the Banyuwangi Regency Cooperatives and MSMEs Office, the Banyuwangi Regency Industry and Trade Office and carried out by the Ministry of Religion. The inhibiting and supporting factors are based on the SWOT analysis: being in the aggressive category in the sense of a very favorable situation.